ANALISIS KELAYAKAN BUDIDAYA SARANG BURUNG WALET DI DESA BADAK BARU KECAMATAN MUARA BADAK (Studi Pada Usaha Sarang Burung Walet Pak Nassarudin) - Ramli, Ramli; Fahleti, Widya; Dewi, Septira (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2024)
Currently, in the Muara Badak sub-district, many people have built swallow nests. This area is suitable for swallow cultivation because of its location close to the beach, nature that is still free from pollution, and close to forests that are still wide open. The high selling price and large capital make it difficult for wallet farmers who are already cultivating or prospective new Sawang wallet farmers to make a decision to invest. Ironically, many end up stopping their business in the middle of the road because they are considered a failure. Therefore, it is necessary to do a business feasibility analysis before starting a business. Sampling was carried out purposively, namely Mr. Nassaruddin's Wallet Nest Business with the consideration that it had been in operation for the last twelve years until 2023 and had a three-level wallet bird's nest building by calculating the NPV, Net B/C, IRR, and PP values. The results of this study are that the yields obtained can reach tens of millions of rupiah, In the financial feasibility analysis based on investment criteria with a factor discount of 10%, it can be produced as follows: NPV value > 0, which is IDR 580,147,000.00, Net B/C value > 1, which is 5.12, IRR value > i, which is 29.21%, and PP value is 6.758 years. These results indicate that Pak Nassarudin's Swallow's Nest Business is feasible to implement or continue.